Outcomes or participation? Experimentally testing competing sources of legitimacy for taxation - Christoph Engel; Luigi Mittone; Azzurra Morreale (Economic Inquiry, 2023)
Legitimacy may result from support for projects that a government implements. However, legitimacy may also result from the opportunity to participate in the selection process of projects. We tested the strength of these competing sources of legitimacy experimentally and their relationship. We find a straightforward effect of the former: the more projects a participant supports, the higher their taxes. Participants are also willing to pay for participation; if they have had a say, they pay higher taxes. Yet, most of this effect is actually instrumental: participants want participation to ensure that their taxes are used for purposes they deem acceptable.
Keywords: 330; experiment; legitimacy; rule following; tax morale